Research of process of absorption of carbon dioxide with water in capillary-porous elements - Svitlyk, Andriy; Prohorov, Alexander (My University, 2015)
Investigated the process of saturation of water carbon dioxide.Mass concentration of carbon dioxide has a linear dependence on the pressure and nonlinear from temperature changes and diameter of capillary. With increasing pressure from 0.4 MPa to 0.6 mass concentration of carbon dioxide in the liquid increases. Mass concentration of the mixture decreases with increasing temperature. With the growth of capillary diameter 10 to 20 mm mass concentration of carbon dioxide in the liquid is reduced. It is connected with the structural formations of water molecules and their oscillating motion. At low temperatures the oscillating motion of the molecular structures of water are not significant and carbon dioxide molecules easily penetrate into these structures without destroying them. The mathematical dependence of the concentration of carbon dioxide in water from pressure, temperature and capillary diameter allows you to adjust the process and determine its rational parameters. Application results in the production of carbonated beverages to increase productivity, reduce the loss of carbon dioxide and increase for foam stability. Досліджувався процес насичення води діоксидом вуглецю. Масова концентрація діоксиду вуглецю має лінійну залежність від тиску і нелінійну від зміни температури та діаметру капіляра. При збільшенні тиску від 0,4 до 0,6 МПа масова концентрація діоксиду вуглецю в рідині зростає. Масова концентрація суміші при зростанні температури знижується. При зростанні діаметру капіляру від 10 до 20 мм масова концентрація діоксиду вуглецю в рідині знижується. Це пов’язане із структурними утвореннями молекул води та їх коливальним рухом. При низьких температурах коливальний рух молекулярних утворень води не значний і молекули діоксиду вуглецю легше проникають в дані структури не руйнуючи їх. Отримана математична залежність концентрації діоксиду вуглецю в воді від тиску, температури та діаметру капіляру дозволяє регулювати процес та визначити його раціональні параметри. Застосування результатів у виробництві газованих напоїв дозволить підвищити продуктивність, зменшити втрати діоксиду вуглецю і підвищити піностійкість.
Keywords: carbon dioxide; capillary; absorption; капіляр; абсорбція; діоксид вуглецю; кафедра машин і апаратів харчових та фармацевтичних виробництв